Diagnostic algorithm for cognitive dysfunction in patients with hypertension in medical and social expertise - Yanovska, Svitlana (Psychiatry, Neurology and Medical Psychology, 2018)
Cognitive impairments (CI) are typical for patients with hypertension (AH), especially who suffered a stroke. Methods to detect CI in patients with AH in general practice of medical and social expertise based on application of advanced technologies (model development for CI assessment, improvement of methods of psychological diagnostics and creating software) have been considered in the paper. The most significant indicators to assess attention, memory, thought process, intelligence, and personality and character traits in patients who suffered a cerebral stroke were identified and demonstrated. Diagnostic algorithm for detecting the nature and stage of cognitive dysfunction in AH patients has been developed to be used in the general practice of medical and social expertise.